Tunable MEMS capacitor: influence of fluids. Issue 2 (1st January 2017) - Habbachi, N.; Boussetta, H.; Boukabache, A.; Kallala, M.A.; Pons, P.; Besbes, K.
Abstract : The effect of a dielectric liquid on the tunability of capacitor operating in RF domains is evaluated. The RF measurement shows a high variation of the resonant frequency accompanied with a low insertion loss. Moreover, the fluid positions between electrodes modify the capacitance value up to Tr = 6660% at 600 MHz. The quality factor decreases in response of water filling from Q max = 51.9 when it is empty to Q min = 1.49 when it is fully filled. According to the finite‐element method analysis, the change of the dielectric permittivity influences the capacitor performances. Essentially, the tuning range of the capacitance and the quality factor could reach, respectively: Tr = 7660% and Q min = 35.